Utilization Of Rubber Seed (Havea bransiliesis) Fermentation As Fish meal of Cyprinus carpio L Fingerling - Abdul Rasyid Lubis; Adelina '; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted for 56 days from June to August 2013. The aimof this research was to find out respons of mas (Cyprinus carpio L) fingerling onrubber seed fermentations. The methods used in this study was an experimentalmethod and RAL one factor with stocking density 0f 5 treatments. The fish used inthis research with size of 3-4 cm in length and 2,35 - 2,37 g in weight. Fish werereared in 60x30x35 cm in aquarium with stocking density of 15/aquarium. Feedingtrials were replacing with soybean meal with rubber seed fermentation applied to 25,50, 75 and 100% for 32% protein content.Result showed that fermentation of rubber seed gave significant effect(P<0,05) on growth, feed efficiency, and protein retentions. Replacement 100% ofrubber seed fermentation is the best respons, produce the highest growth 2.75%, feedefficiency 34.53%, protein retention 59.05%, and 65,28 feed digestion respectively.Key word: Cyprinus carpio, Rubber seed,Fermentation